The Integration of Content Marketing and Storytelling to Enhance Perceived Value and Purchase Intention toward Local Fashion Brands - Meitri Wulandari Djaya Negara; Ragina Gita Amelia; Tezhalonika Marchela; Rusnandari Retno Cahyani (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study investigates the integration of content marketing and storytelling in enhancing perceived value and purchase intention toward local fashion brands. As competition in the digital marketplace intensifies, local fashion businesses are required to adopt marketing strategies that not only communicate product attributes but also establish meaningful emotional connections with consumers. This research employs a systematic literature review approach by analyzing 21 peer-reviewed articles and industry reports published between 2018 and 2025. Data were collected from reputable academic databases, including Google Scholar, ScienceDirect, Emerald Insight, and Springer Link, and were analyzed using thematic synthesis. The findings reveal that content marketing primarily strengthens consumers’ functional perceived value by providing relevant, informative, and consistent product-related information. In contrast, storytelling enhances emotional perceived value through authentic narratives that foster trust, engagement, and brand attachment. The integration of these strategies generates a synergistic effect that significantly increases purchase intention by combining rational evaluation with emotional involvement. The effectiveness of this integration is influenced by message consistency, cultural relevance, and sustained digital engagement across social media platforms. This study contributes to the marketing literature by providing a comprehensive understanding of how informational and narrative-based communication jointly influence consumer behavior. Practical implications suggest that local fashion brands should develop culturally relevant and authentic digital storytelling strategies to strengthen competitive advantage and foster long-term customer relationships.